How well the ICF concepts of functioning, capacity and performance are known amongst the Finnish specialists in physical and rehabilitation medicine? - Mikhail Saltychev; Katri Laimi; Jaro Karppinen (My University, 2022)
Purpose: To investigate how well Finnish specialists in physical and rehabilitation medicine (PRM) are familiar with ICF-based concepts of functioning, capacity, and performance.


Methods: In February 2013, the 5-minute survey was conducted amongst participants at the annual meeting of the Finnish Society of PRM. The 54 participants (response rate 81%) were asked to define the difference between concepts of functioning and capacity/performance. They were also asked to give some examples of medical tests related to these concepts. Two independent researchers evaluated the responses basing on appropriate definitions presented by ICF and researchers own experience.
Results:

Of respondents, 83% were able to define the concept of functioning accordingly to the ICF framework as a complex relationship between health condition and contextual factors. Instead, only 24% were capable to describe concept of capacity/performance as an ability to execute single tasks in a standard or current environment. Of respondents, 40% emphasized the physical dimension of performance. Over 80% of respondents suggested at least one test for assessment of the level of performance, but only 57% introduced an example of tests for measuring limitation of functioning.
Conclusions:
The ICF-based concepts of functioning and performance were not widely used amongst Finnish physicians specialized in PRM even if the responses to survey reflected the biopsychosocial way of understanding the functioning.

The ICF-based concepts of functioning and performance were not widely used amongst Finnish physicians specialized in PRM even if the responses to survey reflected the biopsychosocial way of understanding the functioning.
The ICF-based concepts of functioning and performance were not widely used amongst Finnish physicians specialized in PRM even if the responses to survey reflected the biopsychosocial way of understanding the functioning.